Hyperlipidaemia in Diabetes Mellitus - Khattak, Muhammad Ishaq; Rehman, Faiz ur; Javaid, Muhamamd; Khattak, Zahid (Journal of Postgraduate Medical Institute, 2011)
Diabetes mellitus being a common disorder, having hyperlipidemia as one of major complications was studied. Patients with systemic diseases such as CRF hypertension, nephrotic syndrome, myxoedema and SLE were excluded. Those cases who were on drugs like beta blockers, thiazide diuretics, steroids, alcohol etc were excluded from this study. blood samples from all these established cases were taken for analysis for triglycerides alongwith other lipid profile. Early diagnosis, good glycemic control and dietary modification are usually enough for prevention and treateing hypertriglyceridemia in diabetes mellitus. Exercise not only reduces the serum lipid lelvel but also potentials the effects of diet or drug therapy or glucose metabolism in diabetic patients. When these measures fail then lipid lowering drugs are instituted. HMG Co-A reductase inhibitors are of value in moderate to severe hypertriglyceridemia with coexisting hypercholestrolemia while severe hypertriglyceridemia alone is treated by hypercholestrolemia while severe hypertriglyceridemia alone is treated by fibrates. Muhammad Irfan